Contrasting responses of urban and rural surface energy budgets to heat waves explain synergies between urban heat islands and heat waves. (13th May 2015) - Li, Dan; Sun, Ting; Liu, Maofeng; Yang, Long; Wang, Linlin; Gao, Zhiqiu
Abstract: Heat waves (HWs) are projected to become more frequent and last longer over most land areas in the late 21st century, which raises serious public health concerns. Urban residents face higher health risks due to synergies between HWs and urban heat islands (UHIs) (i.e., UHIs are higher under HW conditions). However, the responses of urban and rural surface energy budgets to HWs are still largely unknown. This study analyzes observations from two flux towers in Beijing, China and reveals significant differences between the responses of urban and rural (cropland) ecosystems to HWs. It is found that UHIs increase significantly during HWs, especially during the nighttime, implying synergies between HWs and UHIs. Results indicate that the urban site receives more incoming shortwave radiation and longwave radiation due to HWs as compared to the rural site, resulting in a larger radiative energy input into the urban surface energy budget. Changes in turbulent heat fluxes also diverge strongly for the urban site and the rural site: latent heat fluxes increase more significantly at the rural site due to abundant available water, while sensible heat fluxes and possibly heat storage increase more at the urban site. These comparisons suggest that the contrasting responses of urban and rural surface energy budgets to HWs are responsible for the synergies between HWs and UHIs. As a result, urban mitigation and adaption strategies such as the use of green roofs and white roofs are needed in order to mitigate the impact of these synergies.